Evidence for a Power Theory of Personal Income Distribution - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2017)
This paper proposes a new `power theory' of personal income distribution. Contrary to the standard assumption that income is proportional to productivity, I hypothesize that income is most strongly determined by social power, as indicated by one's position within an institutional hierarchy. While many theorists have proposed a connection between personal income and power, this paper is the first to quantify this relation. I propose that power can be quantified in terms of the number of subordinates below one's position in a hierarchy. Using this definition, I find that relative income within firms scales strongly with hierarchical power. I also find that hierarchical power has a stronger effect on income than any other factor for which data is available. I conclude that this is evidence for a power theory of personal income distribution.
Keywords: 330; income distribution; hierarchy; power